Ruang Lingkup Etika Islam: Pemetaan Dan Peluang Kajian Akademik - Akmal Nur Hakim; Adhimas Alifian Yuwono (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
The purpose of this research is to provide a strategic map of the scope of Islamic ethics and its academic study opportunities. The formulation of the scope is quite important because the study of Islamic ethics is very broad and the view of good-bad, right-wrong, and should-not-should always encompass the life of a Muslim. For this reason, in order to achieve the direction and depth of the research, a technical guide such as a road map is needed. This research uses a qualitative approach with a document study method that collects various scientific works on the theme of Islamic ethics. With thematic analysis to identify, evaluate, and group the main themes that emerge about Islamic ethics. The result of this research is that the scope of Islamic ethics and its academic study opportunities include: (1) religious ethics, which deals with human behaviour towards Allah and the Prophet. (2) individual ethics, which investigates honesty, patience, discipline, courage, responsibility, etc. about how one fulfils one's obligations. It is about how one fulfils one's obligations to oneself. (3) social ethics, which talks about man's relationship with his fellow man, such as family ethics, friendship ethics, state ethics, to political ethics, economic ethics, and the like. (4) environmental ethics, which discusses the pattern of human relationships with nature along with plants and animals. In this area there are several discourses such as egocentric, ecocentric, theological ethics, ecofeminism, animal rights and Islamic ecoreligious